Strategi Komunikasi DPRD DKI Jakarta Dalam Meningkatkan Citra Instansi Terhadap Publik Melalui Media Sosial Instagram @dprddkijakarta - Darmawan, Ade Septian; Meliala, Robbikal Muntaha; Bender, George Wilhelm (Innovative: Journal Of Social Science Research, 2025)
The communication system between public relations (PR) and the government is inherently one-way, necessitating that all released information be effectively packaged and distributed to the public. The numerous cases reflecting the negative image of DPRD DKI Jakarta members underscore the significance of public relations in developing effective communication strategies with citizens. This study aims to identify and understand the communication strategies used by DPRD DKI Jakarta to enhance its institutional image via its Instagram account, @dprddkijakarta. Utilizing a qualitative descriptive method with a case study approach, the research analyzes how DPRD DKI Jakarta leverages Instagram to improve its public image. Data was collected through passive participant observation, semi-structured interviews, literature review, and documentation from November 19 to December 19, 2024. Key informants include Agus Ermanto (Head of Public Relations Subdivision) and Eko Prabowo (Content Creator), along with Jakarta residents following the Instagram account. Data analysis employed Cyber Media Analysis (AMS) to uncover communication patterns and the effectiveness of social media strategies. Findings reveal that the communication strategy partially aligns with the PENCILS theory, though community involvement and social responsibility aspects remain underdeveloped. SWOT analysis highlighted strengths, weaknesses, opportunities, and threats, ultimately showing successful enhancement of DPRD's image, albeit requiring optimization in theory implementation.